PENATALAKSANAAN DIET PADA NEFROPATI DIABETIK - Kresnawan, Triyani; Darmarini, Ferina (PERSATUAN AHLI GIZI INDONESIA, 2004)
One of the complication of diabetes mellitus is nephropathy diabetic, if this situation is not cured properly it tends to develop the end stage of renal failure. The objectives of this diet management in patients with nephropathy diabetic are to reduce progression of renal damage, maintain the nutritional status of the patient, control blood glucose, lipid serum and maintain electrolyte and fluid balance. Nutrient requirement of nephropathy diabetic patients should contain: protein 0.8 g/kg/body weigh/day. But if patients suffered of end stage of renal failure 0.8 g/kg body weigh/day, in the case of dialysis the protein need is 1-1.2g/kg body weigh/day. For energy requirement they need 35 kcal/kg body weigh/day, with the carbohydrate 60% from total energy need, fat should be 30% total energy need contain poly unsaturated fatty acid and mono unsaturated fatty acid. For mineral, natrium (Na) is needed 1000-3000 mg/day, whereas kalium (K) is 40-70 mEq/day (1600-2800mg/day). In conclusion, diet management is taking an important role to delay the progression of being end stage renal failure.Keywords: nefropati diabetik, gagal ganjal terminal